Social work education: standards of social work practice in the digital age (2022)
The usage of digital technologies in Social Work Education (SWE) entails electronic tools, systems, devices and resources to generate, process and archive information in collaboration with professionals who use digital technology as part of existing strategies. In line with the mission of social work profession, social work education is geared towards producing adequately skilled social workers whose services enhance well-being and help the basic human needs of individuals, families, groups and communities who are vulnerable or living in poverty. Educators and practitioners should be able to use digital technologies effectively in instruction delivery and training of social workers in this Fourth Industrial Revolution (4IR) era. As digital technologies become more integrated in social work, this paper presents an outline of challenges that practitioners should consider for social workers to incorporate digital technologies into their education and field practice. The paper also discusses potential challenges in the acceptance of digital technology, as well as suggestions for improving its usage in education and practice